FRECOL: Educational Toolbox for Power System Frequency Control - Cecilio,IM; Thornhill,NF (2013)
FRECOL is an educational tool for long-term dynamic simulations of power system frequency control under realistic disturbance scenarios. It is implemented in MATLAB/Simulink and is aimed at power and control engineering students to practice frequency control and to test tuning and control strategies.